The Role of Open Innovation and Intellectual Capital on Business Sustainability: Study of Furniture MSMEs in Banjarmasin, Indonesia - Hamdani Arief; Anisah, Hastin Umi (Open Access Indonesia Journal of Social Sciences, 2024)
Furniture MSMEs in Banjarmasin City face various challenges in achieving business sustainability. This research aims to identify and analyze the influence of open innovation on the sustainability of the MSME furniture business and analyze the influence of intellectual capital on the sustainability of the MSME furniture business. This research used a quantitative method by distributing questionnaires to 50 respondents, namely owners and managers of furniture MSMEs in Banjarmasin City. The sampling technique uses non-probability sampling with purposive sampling. Data analysis used descriptive analysis and PLS-based SEM with SmartPLS4.0. Open innovation (X1) and intellectual capital (X2) have a positive and significant influence on business sustainability (Y). In conclusion, open innovation and intellectual capital are important factors that contribute to the sustainability of the MSME furniture business in Banjarmasin City.